Doppler Effect and Acoustic Trails of Neutrinos - Askold Sergeevich Belyakov (Journal La Multiapp, 2022)
In the monitoring mode, signals averaged over 1 minute were recorded in four one-third octave bands: 30, 160, 500 and 1200 Hz. Sometimes, audio signals were recorded using a computer sound card. These signals had varied and surprising forms, but there was no technical capability to record them in monitoring mode. This opportunity appeared in California in 2015. In the period from 2015 to 2017, in the SAFOD pilot well in California at a depth of 1000 m with coordinates 35.974257 N, -120.552076 W, seismological surveys were carried out for the first time using the innovative MIG-3V geophone with a wide band in the infrasonic and sound frequency ranges and in the amplitude range of more than 240 dB. In August 2016, a similar geophone for the same purpose was installed in the VGS well with coordinates 56.967017 N, 43.720605 E to a depth of 1400 m. Digital data in the automatic monitoring mode was recorded continuously every 0.1 ms. Analysis of the data obtained in the SAFOD well (more than 4 TB) showed that, along with seismic signals, there are acoustic traces in the data, which have never been observed in the wells before. Similar tracks were observed in the VGS well. Acoustic trails similar in shape and frequency are observed in the aquatic environment of lakes and Oceans when searching for acoustic trails from high-energy cosmic particles, in particular, with the help of acoustic neutrino detectors.